GAMBARAN PENGETAHUAN DAN PERILAKU PENCEGAHAN SUNBURN PADA ANAK DARI WISATAWAN MANCANEGARA DI WILAYAH KUTA UTARA KABUPATEN BADUNG - Putu Mega Krisnayanti; Kadek Cahya Utami; Ni Putu Emy Darma Yanti Yanti (Coping: Community of Publishing in Nursing, 2021)
Sunburn is an erythema on the skin with a history of direct sun exposure especially UV radiation which can cause skin cancer. Risk factors for sunburn are more common in young people especially children so prevention is needed to protect themselves from sunburn. Efforts to prevent sunburn by foreign tourists can be influenced by knowledge and behavior. This study aims to describe the knowledge and behavior of sunburn prevention in children of foreign tourists in the North Kuta area of Badung Regency. This research is a simple descriptive study with quantitative methods with cross sectional approach. The sample in this study is the number of foreign tourists who bring their children to visit the North Kuta Region by using consecutive sampling and obtained a sample of 96 foreign tourists. Based on the results of the study, the median age of children of foreign tourists is the age of 6 years with the youngest age is 0 years and the oldest age is 12 years. The results of statistic test show that the middle value of knowledge score obtained from the children of foreign tourists in the North Kuta area is 12 with the highest score of 17 and the lowest score of 4 and most of the children of foreign tourists have behaved to prevent sunburn or have taken precautions to avoid skin from sunburn. This research is expected to be a reference for health workers in the tourist clinic to provide education to foreign tourists about sunburn prevention.